Genotoxic risk in occupational exposure to petrol and its amelioration by vitamin C and vitamin E. Issue 6 (2nd June 2022) - Shaikh, Amrin; Chandel, Puranjay; Chandel, Divya
Abstract: Petrol contains mixture of mutagens and carcinogens which have potential health risk after prolonged occupational exposure. We have compared genotoxicity and its amelioration in blood samples from 70 petrol pump attendants, working in congested area of the Ahmedabad city, India and similar number ( n = 70) of Control samples from office workers dwelling in less polluted areas of the city. The cytokinesis-block micronucleus assay showed highly significant frequencies of micronucleus in Exposed than in the Controls. The sister chromatid exchanges were also significantly increased while the cell cycle proliferative index was significantly decreased in the Exposed individuals than the Controls. Addition of standardized doses of vitamin C and vitamin E in the lymphocyte cultures ( in vitro ) significantly improved all the biomarkers. The long-term occupational petrol exposure causes genotoxic effects and use of vitamins C and E for protection should be further explored in randomized controlled studies.